Determinant of Behavioral Intention to Use Digital Zakat Payment: The Moderating Role of Knowledge of Zakat - Cahyani, Utari Evy; Sari, Dia Purnama; Afandi, Ahmad (UIN Sunan Kudus, 2022)
The potential for zakat in Indonesia is increasing over time. However, the value of the increase in zakat receipts is not proportional to the potential of zakat. Research on zakat behavior using digital platforms is important considering the lack of realization of zakat collection compared to the existing potential. This study develops the UTAUT model by adding knowledge of zakat as a moderated variable. A quantitative approach is used in this research. The number of respondents in this study was 200 who were obtained through convenience sampling based on questionnaires distributed online. Data analysis was performed using partial least square-structural equation modeling (PLS-SEM). The results showed that performance expectancy, social influence, and facilitating conditions had a positive effect on behavioral intention to use digital zakat payment. Meanwhile, the moderating effect shows that knowledge of zakat moderates the relationship between performance expectancy and behavioral intention. These results have implications for the need to increase the effectiveness of digital zakat payments, have influencers who educate about zakat payments using digital, and increase the choice of zakat management institutions that accommodate digital payments so that the intention of muzakki to pay zakat using digital payments is increasing. The moderating effect implies that for muzakki who have higher knowledge of zakat, the level of trust and effectiveness of digital payments can increase the desire to pay zakat through digital payments.